2013
DOI: 10.1002/jcp.24448
|View full text |Cite
|
Sign up to set email alerts
|

EBV‐Encoded LMP‐1 Sensitizes Nasopharyngeal Carcinoma Cells to Genotoxic Drugs by Down‐Regulating Cabin1 Expression

Abstract: The oncogenic latent membrane protein 1 (LMP1) of Epstein-Barr virus (EBV) is involved in the pathogenesis of human nasopharyngeal carcinoma (NPC) and lymphoma. We and other authors have shown earlier that LMP1 induces apoptosis and inhibits xenograft tumor growth in mice, but the mechanism underlying these processes has not been investigated so far. In the present study, we show that knockdown of LMP1 renders the EBV-positive NPC cell line CG-1 resistant to various genotoxic drugs (cisplatin, etoposide, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Treatment with chemotherapeutic drugs activates several biochemical signaling pathways, including the c-Jun N-terminal kinase (JNK) pathway (5). JNKs are serine/threonine kinases that belong to the mitogen-activated protein kinase family (6), and are responsive to diverse stress (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with chemotherapeutic drugs activates several biochemical signaling pathways, including the c-Jun N-terminal kinase (JNK) pathway (5). JNKs are serine/threonine kinases that belong to the mitogen-activated protein kinase family (6), and are responsive to diverse stress (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that LMP1 have double effects: the cytotoxic and oncogenic effects [57,58]. Although Pu-Yuan Chang et al [59] found that LMP1 can sensitize nasopharyngeal carcinoma cells to genotoxic drugs (cisplatin, etoposide, and adriamycin), but the cell line CG-1 in above study was difference from the cell lines used in our study including the region, histopathology and the way of EBV infection. Guillaume Brocqueville et al [60] found that the cytotoxic and oncogenic effects of LMP1 are not mutually exclusive but may operate sequentially.…”
Section: Discussionmentioning
confidence: 52%
“…Currently, many studies have identified proteins or genes in chemotherapy-resistant NPC, [32][33][34][35] but only the differences between the drug-resistant cell and its parent cell are discussed. 32 In this study, we established two drug-resistant cell lines at the same time to screen for differences common to both cell lines.…”
Section: Discussionmentioning
confidence: 99%